The Grinnell ice-cap / Fieldiana Geology v.7, no.1 - Roy, Sharat Kumar, 1897-1962 (Chicago : Field Museum of Natural History, 1937)
Fieldiana series has been published as Geological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Geology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).